2011
DOI: 10.1371/journal.pone.0018759
|View full text |Cite
|
Sign up to set email alerts
|

Non-Esterified Fatty Acids Generate Distinct Low-Molecular Weight Amyloid-β (Aβ42) Oligomers along Pathway Different from Fibril Formation

Abstract: Amyloid-β (Aβ) peptide aggregation is known to play a central role in the etiology of Alzheimer’s disease (AD). Among various aggregates, low-molecular weight soluble oligomers of Aβ are increasingly believed to be the primary neurotoxic agents responsible for memory impairment. Anionic interfaces are known to influence the Aβ aggregation process significantly. Here, we report the effects of interfaces formed by medium-chain (C9–C12), saturated non-esterified fatty acids (NEFAs) on Aβ42 aggregation. NEFAs uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 69 publications
3
72
0
Order By: Relevance
“…This property has been recently demonstrated by Kayed et al (28), who reported that specific soluble oligomers called PFOs were able to seed their own replication upon interacting with monomeric A␤. The property of replication could be a manifestation of the unique structure of the oligomeric assembly and more importantly may complement our previously reported hypothesis that such oligomers are formed along a pathway different from fibril formation (1,19). To explore this, a 20 M sample of freshly purified, "seedfree" A␤42 was incubated with 0.4 M isolated LFAOs as seeds (2% molar ratio) at room temperature.…”
Section: Lfaos Are Replicating Strainsmentioning
confidence: 57%
See 4 more Smart Citations
“…This property has been recently demonstrated by Kayed et al (28), who reported that specific soluble oligomers called PFOs were able to seed their own replication upon interacting with monomeric A␤. The property of replication could be a manifestation of the unique structure of the oligomeric assembly and more importantly may complement our previously reported hypothesis that such oligomers are formed along a pathway different from fibril formation (1,19). To explore this, a 20 M sample of freshly purified, "seedfree" A␤42 was incubated with 0.4 M isolated LFAOs as seeds (2% molar ratio) at room temperature.…”
Section: Lfaos Are Replicating Strainsmentioning
confidence: 57%
“…Briefly, 1.5-2 mg of peptide was dissolved in 0.5 ml of 30 mM NaOH and stored for 15 min at room temperature prior to size exclusion chromatography (SEC) onto a 1 ϫ 30-cm Superdex-75 HR 10/30 column (GE Healthcare) attached to an ÄKTA FPLC system (GE Healthcare) to remove any preformed aggregates as reported previously (1). The column was preequilibrated in 20 mM Tris-HCl (pH 8.0) at 25°C and run at a flow rate of 0.5 ml/min.…”
Section: Preparation Of A␤42 Monomersmentioning
confidence: 99%
See 3 more Smart Citations